Prevalence of renal dysfunction in ischaemic stroke and transient ischaemic attack patients with or without atrial fibrillation - Laible, Mona; Horstmann, Solveig; Rizos, Timolaos; Rauch, Geraldine; Zorn, Markus; Veltkamp, Roland (European journal of neurology, 2015)
Chronic kidney disease (CKD) is associated with a higher risk of stroke and atrial fibrillation (AF). There are limited data on the comorbidity of renal dysfunction and AF in stroke patients. Our aim was to determine the frequency of kidney dysfunction in ischaemic stroke patients with and without AF.
First published: 04 August 2014
Gesehen am 08.06.2020